Motivations, experiences and perceptions on use of pornographic materials of adolescent males from selected universities in Metro Manila - Duran, Gabriel Angelo del Rosario; Yuzon, Francis Albert Barnuba; Agustin, Estrella R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The purpose of this study is to determine the various motivations, experiences and perceptions that adolescent males have when it comes to the use of pornographic materials. The researchers interviewed 30 adolescent male students from selected universities in Metro Manila. The objective was to know how they were first exposed to pornographic materials, their history of usage during grade school/elementary and high school, their current usage in college, and their perceptions on their use of pornographic materials and how it affects them and their lives. It appeared that the first exposure of the adolescent males to pornography was generally during the fifth grade. This first exposure usually happens at home, and is facilitated by the friends and classmates of the one exposed. Offline video sources such as CDs and phone videos are the common mediums used for exposure. Usage of pornographic material increased from grade school to high school, with monthly usage during grade school to a weekly usage in high school. Medium used also shifted from offline video sources to online sources, and is attributed by the respondents to an increase in accessibility to cheaper and faster internet when they were in high school. There was a decrease of usage during college, usually done only twice or thrice a week. Boredom and sexual urges are pointed as the main reasons and motivations as to why they access pornographic materials. Common forms used are still online sources. Majority of the respondents indicated that they tried to curb their usage. A third of those who tried reported complete success and another third reported that they were in control while still using pornographic materials, while the last third reported that they were unsuccessful. There were reported positive and negative effects of pornography in their way of living and relationships.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Teenage boys -- Philippines; Pornography in popular culture -- Philippines